To Be Cytosolic or Vacuolar: The Double Life of Listeria monocytogenes - Bierne, Hélène; Milohanic, Eliane; Kortebi, Mounia (Frontiers in Cellular and Infection Microbiology, 2018)
Intracellular bacterial pathogens are generally classified into two types: those that exploit host membrane trafficking to construct specific niches in vacuoles (i.e., “vacuolar pathogens”), and those that escape from vacuoles into the cytosol, where they proliferate and often spread to neighboring cells (i.e., “cytosolic pathogens”). However, the boundary between these distinct intracellular phenotypes is tenuous and may depend on the timing of infection and on the host cell type. Here, we discuss recent progress highlighting this phenotypic duality in Listeria monocytogenes, which has long been a model for cytosolic pathogens, but now emerges as a bacterium also capable of residing in vacuoles, in a slow/non-growing state. The ability of L. monocytogenes to enter a persistence stage in vacuoles might play a role during the asymptomatic incubation period of listeriosis and/or the carriage of this pathogen in asymptomatic hosts. Moreover, persistent vacuolar Listeria could be less susceptible to antibiotics and more difficult to detect by routine techniques of clinical biology. These hypotheses deserve to be explored in order to better manage the risks related to this food-borne pathogen.